Analysis of Hygiene, Health and Safety in Natural Tourist Attractions Based on the Decree of the Minister of Health Number HK.01.07/Menkes/382/2020 concerning Health Protocols for the Community in Public Places and Facilities in the Context of Prevention - Fransisca Ully Marshinta (HOLISTICS, 2021)
Tourism is usually synonymous with pleasure but this activity also has risks, especially during the COVID- 19 pandemic, so attention and improvement are needed on aspects related to tourism services such as infrastructure, security, safety and health (K3) and conservation of the tourism environment. The research method used is a normative research study that departs from the study of legal rules related to tourism legislation. Nature tourism is one of the tourist attractions in Indonesia today, which is visited by many people, even though in an atmosphere of COVID-19. Every tourist attraction destination is obliged to create cleanliness, health and safety in managing tourist attraction destinations during the COVID-19 pandemic, especially nature tourism that is in the open by following the Decree of the Minister of Health Number HK.01.07/Menkes/382/2020 concerning Protocol Public Health in Public Places and Facilities in the Context of Prevention and Control of Corona Virus Disease 2019 (Covid-19). So that visitors to nature tourism feel safe and comfortable when visiting nature tourism. Keywords: Tourism Law, K3, Nature Tourism